GELASTIC SEIZURES PADA HEMIATROPI SEREBRI KIRI - Donny H. Hamid*, Ridwan*, Gotot Sumantri*, Melita** (NEURONA, 2010)
SEIZURES ARE EPILEPTIC SEIZURES CHARACTERIZED BY PATHOLOGIC LAUGHTER AS A MAIN CLINICAL MANIFESTATION AND ARE UNCOMMON AMONG EPILEPSY GELASTIC SEIZURES ARE ALSO DESCRIBED IN PATIENTS WITHOUT HYPOTHALAMIC HAMARTOMA IN WHOM A PROVEN OR SUSPECTED SEIZURES FOCUS LIES IN THE FRONTAL OR TEMPORAL LOBES OR WHERE THE ORIGIN OF THE SEIZURES REMAINS UNDETERMINED ALTHOUGH INAPPROPRIATE IT CAN BE SO SIMILAR TO THE NATURAL LAUGHTER AND IF LAUGHTER IS THE ONLY SYMPTOM CAN BE SUPPOSED AS A PSYCHIATRIC DISEASE